The effects of various impurities on calcium phosphate crystallization - Kara, Ayça (My University, 2018)
Bu çalışmada, hydroksiapatit (HAP) kristalizasyonu kesikli bir kristalizörde, saf ve katkı maddeleri varlığında incelenmiştir. Katkı maddesi olarak valerik asit ve hidroksipropil beta siklodekstrin kullanılmıştır. Deneyler 100, 500 ve 1000 ppm konsantrasyonlarında gerçekleştirilmiştir. Deneyler sonunda elde edilen HAP kristallerinin karakterizasyonu XRD, SEM, TEM, FTIR, BET ve zeta potansiyel ölçümleriyle yapılmıştır. Ayrıca, HAP kristallerinin termal bozunma davranışları termogravimetrik analiz (TGA) yöntemiyle incelenmiş ve elde edilen veriler yardımıyla aktivasyon enerjileri Kissinger modeli kullanılarak hesaplanmıştır. Coats Redfern modeli yardımıyla termal bozunma mekanizması detaylı olarak incelenmiştir. Karakterizasyon ve termal bozunma kinetik sonuçları, hem valerik asitin hem de hidroksipropil beta siklodekstrin’in HAP kristallerinin fiziksel, morfolojik ve termal özelliklerini etkilediğini ortaya koymuştur.

In this study, hydroxyapatite (HAP) crystallization was examined in a batch crystallizer in the presence of pure and additive media. Valeric acid and hydroxypropyl beta cyclodextrin were used as the additives. The experiments were carried out at concentrations of 100, 500 and 1000 ppm additives. The characterization of HAP crystals, obtained the end of the experiments, were made by X-Ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) and zeta potential measurements. Also, thermal degradation behavior of HAP crystals was examined by thermogravimetric analysis (TGA) method and activation energies were calculated by using of Kissinger model with the help of obtained data. Thermal degradation mechanism was determined in detail by the help Coats Redfern model. Characterization and thermal degradation kinetic results revealed that both valeric acid and hydroxypropyl beta cyclodextrin affected physical, morphological and thermal characteristics of HAP crystals.
Keywords: characterization; Chemical engineering; crystallization; hidroksiapatit; hidroksipropil beta siklodekstrin; hydroxypropyl beta cyclodextrin; karakterizasyon hydroxyapatite; Kimya mühendisliği; kristalizasyon; valeric acid; valerik asit